SOME EARLY ACCOUNTANCY EXAMINERS. - Webster, Norman E. (The Accounting Review, 1944)
Abstract In the ten years from 1896 to 1905, seven states of the U.S., had issued 644 certificates, largely, of course, upon waiver of examination. In that period the examiners in those states had decided upon subjects and scope of their examinations, and in each state they had prepared, given and rated from one to twenty examinations. Quite likely their bases for ratings differed, but they were in complete agreement upon the scope of the tests. In those first ten years all examinations were in four subjects, Commercial Law, Commercial Law, Practical Accounting and Auditing. Later some states added a few related subjects. In 1907 Pennsylvania combined the last three subjects into one test entitled "General Accounting," and from 1916 to 1942 those states which used the service of the American Institute of Accountants combined the second and third subjects into Accounting Theory and Practice. At the present time in 1943, the fifty-two Boards of Examiners are composed of one hundred and ninety-seven members besides the nine members of the Board of Examiners of the American Institute of Accountants. In 1905 the nine boards then existing were composed of twenty-nine accountant members.